PENGARUH PHARMACIST SERVICES TERHADAP LOYALTY MELALUI SATISFACTION PADA APOTEK PEMERINTAH DI KOTA AMBON - Imelda Ongkiwijaya (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
This research discusses about the influence of Pharmacist Services toward Loyalty through Customer Satisfaction to the Government Pharmachy in Ambon. The objectives of this research were 1) to analyze the influence of Pharmacist Services toward Customer satisfaction, 2) to analyze the influence of Customer satisfaction toward Customer Loyalty, 3) to analyze the influence of Pharmacist Services toward Customer loyalty. These objectives were researched through 200 respondents who satisfy: ages above 17 years old and consumers who have come to government pharmachy in Ambon at least two times in three months. Respondents were chosen using purposive sampling method and the data collected were analysed using AMOS version 21.0 and SPSS version 13.0. The proposed model was tested through Structural Equation Modelling (SEM) and was analyzed using AMOS version 21.0. The result of This research showed that 1) pharmacist services was found to have positive effect on customer satisfaction, 2) customer satisfaction was found to have positive effect on loyalty, 3) pharmacist services was found to have positive effect on customer loyalty. Keywords: Pharmacist services, Customer satisfaction, Loyalty, Government pharmachy in Ambon.